Effect of Repeated Cold Water Swimming Exercise on Adaptive Changes in Body Weight in Older Rats - Iwona Bryczkowska; Irena Baranowska-Bosiacka; Anna Lubkowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
The aim of this study was verification whether an 8-week-long swimming exercise training would induce adaptive changes in body weight in rats and whether possible changes would depend on aquatic environment temperature and animal sex. The exercisetrained groups swam 4 minutes a day, five days a week during eight week of housing. Exercise was performed by swimming in glass tanks containing tap water maintained according to group at 5 ±2°C (cold group) and 36 ±2°C (thermal neutral group). Before and after each week of the experiment, rats were weighed. When comparing the nature of changes in the body weight of rats exposed to swimming exercise training in cold water, attention should be paid to their dependence on sex. There were statistically significant changes in the nature of changes in body weight between male rats and female rats of the cold group (5°C) as early as experimental week 2 until the end of the experiment (p < 0.001). Interestingly, the females exposed to swimming exercise training at 5°C were the only group in which an increase in body weight occurred during experimental week 8 in relation to baseline values.